Using visual metaphors in advertising campaigns to promote sustainable tourism - Kamel,Noha Ahmed (2024)
Abstract Visual metaphors are utilised in advertising campaigns to convey knowledge more imaginatively without sacrificing context. The current study investigates the feasibility of using visual metaphors in green advertising campaigns promoting sustainable tourism in Egypt. Using a mixed-method approach, the current study is conducted in two phases. Phase one analyses the 2021 campaign "A Civilisation Inspired by Nature," utilising a checklist and rhetorical analysis guided by an interpretivist approach. A positivist approach was then employed to collect quantitative data by statistically evaluating the responses provided by the participants on the checklist. Two distinct groups were purposefully chosen: individuals with diverse knowledge backgrounds and experts in history and heritage. To ascertain whether there were any statistically significant differences in the participants' interpretations of the metaphorical themes, we employed independent t-tests for sample analysis. The results show that the campaign successfully employs visual metaphors derived from ancient Egyptian culture to convey the significance of valuing nature and sustainability. Nevertheless, certain difficulties arose in comprehending the metaphorical themes. The current study offers practical insights for marketers on the utilisation of visual metaphors in green advertising campaigns that promote sustainable tourist practices.